2013
DOI: 10.3126/jer.v3i2.8399
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Relations Among Ethnically Diverse University Students in Ethiopia

Abstract: This study focused on examining the intergroup relations among ethnically diverse university students. The study was conducted in Bahir Dar University, one of the public universities in Ethiopia– a country of “indigenous ethnic diversity”. The participants were students, teachersand support staff selected usingpurposive and snowball sampling.The necessary data were collected throughinterview andfocus group discussion. The studyrevealed different factors that are internal and external to the university facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Participants indicated that in practice, Ethiopian university leaders lack the courage and commitment to promote and raise awareness about diversity, let alone address serious challenges of ethnic tensions and conflicts. A previous study in Ethiopia also indicated that higher education leaders fail to promote diversity mainly because of a lack of diversity management skills and fear of politicization of diversity-related issues (Adamu, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Participants indicated that in practice, Ethiopian university leaders lack the courage and commitment to promote and raise awareness about diversity, let alone address serious challenges of ethnic tensions and conflicts. A previous study in Ethiopia also indicated that higher education leaders fail to promote diversity mainly because of a lack of diversity management skills and fear of politicization of diversity-related issues (Adamu, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, summarizing recent ethnic and other diversity-related conflicts at Ethiopian Public Universities, Ethiopia newspaper on November 11, 2018, summarized and reported that: there were clashes between Tigray and Oromo students at Addis Ababa University (AAU) in 2009 which caused injuries on several students; three students were killed and more than forty were injured due to an ethnic-based clash between Amhara and Oromo students at Assosa University in 2017; one student was killed and several injured in Adigrat University on November 2017 due to ethnic-based clash among students; two students killed at Wollega University on December 2017; several injured and blocks of the university put on fire due to clashes between Amhara and Tigray region students at Woldia University on November 2017, and seven were injured due to the clash between Oromo and Southern nation and Nationalities people students at Wachemo University on January 2018. Some local studies indicated that causes of ethnic conflict are generally related to the ethnic polarization, political rivalry and historical relationship among ethnic groups (Abebaw, 2013a(Abebaw, , 2013b and playing religious songs and holding religious practices like group prayers by some students which create discomfort for the others in dormitories is the cause for religious conflicts among students (Arega & Mulugeta, 2017). More importantly, it is argued that public universities of Ethiopia do not have clear plan and strategy for managing their students' body diversity and the measures they took to mitigate diversity-related problems such as tension and conflicts are not effective and efficient which needs further investigation (Abebaw, 2014;Abebaw & Tilahun;Hailemariam, 2016).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The transition of power has not resulted in long-term peace, stability, or solidarity in the country. Since the new prime minister came to power, violent ethnic conflicts and mass killings against ethnic Amhara people have been a routine practice in Tigray, Oromia, and Benishangul Gumuz regions (Adamu, 2013).…”
Section: Introductionmentioning
confidence: 99%